Ipsilateral Uterine Artery Access Through Unilateral Transfemoral Approach Using Simple-Curve Catheter - Lal, Anupam; Vijayvergiya, Rajesh; Singhal, Manphool (Indian Journal of Radiology and Imaging, 2023)
Uterine artery embolization (UAE) is a technique for management of various obstetrical and gynecological problems. Transfemoral approach (TFA) is preferred which can be unilateral or bilateral; however, unilateral puncture is preferred due to lesser chances of puncture-related complications as compared to bilateral puncture. UAE through unilateral TFA is possible with use of reverse loop catheters (Roberts uterine catheter [RUC] or Gandras catheter) to access ipsilateral uterine artery. Other way of cannulating the ipsilateral uterine artery is by maneuvering catheters to form Waltman's loop/Simmon's reverse loop. With advent of RUC, unilateral TFA became standard of care. In the recent past, RUC was retracted from Indian market and its nonavailability had mandated use of either bilateral TFA or use of catheters and techniques used in the past for unilateral TFA. Herein, we describe a technique of doing UAE by unilateral TFA using simple gentle curve catheter (Picard) by making a reverse curve loop.
Keywords: uterine artery embolization; transfemoral approach; 5F-Picard catheter; 0.035 curved-tipped hydrophilic guidewire; reverse loop